Graduates in/for a multicultural and globalising world. Issue 2 (4th June 2018) - Killick, David
Abstract : Purpose: This paper aims to question the terminology, modelling and vagueness surrounding the notion of "global citizen" and argues for the more holistic construct of global selfhood as a legitimate goal for graduates who must make their way in a multicultural and globalising world. Design/methodology/approach: This paper draws upon established education and global citizenship theories to present a model of global graduate attributes. Using this theoretical model, practice implications for learning and teaching in higher education are presented. Findings: This paper proposes some radical transformations to current practice. Practical implications: Proposals within the paper offer academics and academic developers tools for reflection on and transformation of practice. Originality/value: This paper takes forward the often reductive construct of "global citizen" and demonstrates how a more holistic notion of global self can be applied to higher education and graduate outcomes.